Fabrication of anion exchange membrane: a preliminary study - Sarmidi, Mohamad Roji (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
The objective of the work was to fabricate an anion exchange membrane, which can be used for electrodialysis process. The anion exchange membranes were fabricated by means of solution casting method using polysulfone as the binder and anion exchange resin as the polyelectrolyte. The membranes characteristics and performance of the fabricated membranes were evaluated and compared with the commercial anion exchange membranes. The membrane thickness, permselectivity, water content, ion exchange capacity, concentration of ion exchange group and morphological properties of the membranes were studied. The results showed that the percentage of anion exchange resin determine the capacity of ion exchange, percentage of permselectivity and capacity concentration of ion exchange group.